2015
DOI: 10.1039/c5gc01549a
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethylenediamine (HMDA) from fossil- vs. bio-based routes: an economic and life cycle assessment comparative study

Abstract: A series of biobased routes are critically scrutinized for the production of hexamethylenediamine (HMDA) using 5-hydroxymethylene furfural (HMF) as intermediate building block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 28 publications
(11 reference statements)
0
60
0
Order By: Relevance
“…Besides being fully renewable, at the end of its proposed applications, rice husk can be still be used for generating energy or in different manufacturing sectors in accordance with the circular economy principles. Moreover, a bio-based routes for HMDA production has been recently reported, along with the corresponding Life Cycle Assessment 40 . On that respect, application of RH carriers in food sector would enable its use as fertilizer, medium for gardening, ruminant feed or source of fiber in pet foods.…”
Section: Preliminary Evaluation Of the Greenness Of Rh As Enzyme Carriermentioning
confidence: 99%
“…Besides being fully renewable, at the end of its proposed applications, rice husk can be still be used for generating energy or in different manufacturing sectors in accordance with the circular economy principles. Moreover, a bio-based routes for HMDA production has been recently reported, along with the corresponding Life Cycle Assessment 40 . On that respect, application of RH carriers in food sector would enable its use as fertilizer, medium for gardening, ruminant feed or source of fiber in pet foods.…”
Section: Preliminary Evaluation Of the Greenness Of Rh As Enzyme Carriermentioning
confidence: 99%
“…The acetone–butanol–ethanol fermentation process of lignocellulosic biomass supplies appropriate alcohols like butanol, which can be readily oxidized to form butyraldehyde as intermediate for the TMP synthesis . Prominent members of bio‐based amine curing agents include diamines like hexamethylene and isophorone diamine as well as multifunctional aminoalcohols prepared by amination of bio‐based glycidylethers with ammonia …”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] Prominent members of bio-based amine curing agents include diamines like hexamethylene and isophorone diamine as well as multifunctional aminoalcohols prepared by amination of bio-based glycidylethers with ammonia. [ 27,37 ] In spite of the surging number of publications relating to NIPU and polyhydroxyurethane chemistry, few reports address the production of NIPU foams. In the absence of isocyanate groups, NIPU does not enable foaming by liberation of CO 2 typical for isocyanate-based PU preparation in the presence of water.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, various diamines such as ethylenediamine (EDA), hexamethylene diamine (HMDA), isophorone diamine (IPDA) and Jeffamine (D230) were selected to react with the high carbonate content of gallic acid-based cyclic carbonate (compound 2) to form high cross-linked NIPU networks. Especially, hexamethylene diamine (HMDA), which could be produced from bio-based routes, provides a promising way to prepare full bio-based NIPU [47]. It has been reported that the reactions of amines with ester function of cyclic carbonate, resulting in a side reaction with the formation of amide groups, and the side reaction was strongly affected by the temperature of polymerization [11,48].…”
Section: Fig 4 Ft-ir Spectra Of Nipu(1) Prepared At Different Tempermentioning
confidence: 99%